Is a normal computed tomography pulmonary angiography safe to rule out acute pulmonary embolism in patients with a likely clinical probability? - van der Hulle, Tom; van Es, Nick; den Exter, Paul L.; van Es, Josien; Mos, Inge C. M.; Douma, Renée A.; Kruip, Marieke J. H. A.; Hovens, Marcel M. C.; ten Wolde, Marije; Nijkeuter, Mathilde; ten Cate, Hugo; Kamphuisen, Pieter W.; Büller, Harry R.; Huisman, Menno V.; Klok, Frederikus A. (Thrombosis and Haemostasis, 2017)
A normal computed tomography pulmonary angiography (CTPA) remains a controversial criterion for ruling out acute pulmonary embolism (PE) in patients with a likely clinical probability. We set out to determine the risk of VTE and fatal PE after a normal CTPA in this patient category and compare these risk to those after a normal pulmonary angiogram of 1.7% (95%CI 1.0–2.7%) and 0.3% (95%CI 0.02–0.7%). A patient-level meta-analysis from 4 prospective diagnostic management studies that sequentially applied the Wells rule, D-dimer tests and CTPA to consecutive patients with clinically suspected acute PE. The primary outcome was the 3-month VTE incidence after a normal CTPA. A total of 6,148 patients were included with an overall PE prevalence of 24%. The 3-month VTE incidence in all 4,421 patients in whom PE was excluded at baseline was 1.2% (95%CI 0.48–2.6) and the risk of fatal PE was 0.11% (95%CI 0.02–0.70). In patients with a likely clinical probability the 3-month incidences of VTE and fatal PE were 2.0% (95%CI 1.0–4.1%) and 0.48% (95%CI 0.20–1.1%) after a normal CTPA. The 3-month incidence of VTE was 6.3% (95%CI 3.0–12) in patients with a Wells rule >6 points. In conclusion, this study suggests that a normal CTPA may be considered as a valid diagnostic criterion to rule out PE in the majority of patients with a likely clinical probability, although the risk of VTE is higher in subgroups such as patients with a Wells rule >6 points for which a closer follow-up should be considered.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Pulmonary embolism; computed tomography; diagnosis; safety